The ever storms - Foody, Amanda (Foody, Amanda. Wilderlore, 2023)
Thirteen-year old Barclay and his fellow Lore Keeper apprentices are excited to travel to the Desert to study at the respected University of Al Faradh, but when dangerous, unnatural sandstorms and a magical library appear, more than their exams are at stake.